Experimental Study on the Size Effect on the Probability Distribution of Concrete Compressive Strength - Youcheng Zhai (Advances in Civil Engineering)
Understanding the size effect on the probability distribution of concrete compressive strength is critical to accurately determining its probability distribution and to correctly calculating reliability. Compressive strength tests were performed on concrete cubic specimens with side lengths of 70 mm, 100 mm, and 150 mm, respectively. The Kolmogorov-Smirnov test results revealed that concrete compressive strength of each specimen size followed a normal probability distribution; that is, a change in specimen size did not affect the type of probability distribution. The point and interval estimates of the mean and standard deviation of concrete compressive strength showed that both the mean and standard deviation decreased, and the latter decreased to a greater extent with an increase in specimen size. The calculation results show that the standard value of concrete compressive strength also has a significant size effect, but the standard value increases with an increase in specimen size, which is opposite to the change pattern of concrete compressive strength mean and standard deviation. Finally, a reliability analysis was carried out using the compressive strength of a cubic concrete specimen with a size of 150 mm as an example, and the probability distributions for different specimen sizes were found to have a great influence on the reliability of the calculation results. Therefore, it is important to account for the size effect on the probability distribution of concrete compressive strength in practical engineering.